2018
DOI: 10.1038/s41598-018-34289-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of anxiety on emotional recognition: evidence from an ERP study

Abstract: Anxiety-related bias in the recognition memory based on trait anxiety has induced some studies. Their results, however, were conflicting. In fact, anxious differences not only differed from personality traits but also from different anxiety mood levels. We explored the emotional memory bias in both trait and state anxiety individuals, the high trait and high state anxiety group, the high trait and low state anxiety group, the low trait and high state anxiety group, and the low trait and low state anxiety group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 79 publications
1
10
1
Order By: Relevance
“…According to previous studies, nearly one-half of people diagnosed with depression will also experience comorbid anxiety ( 81 ). Anxiety is one of the most common mental health diseases contributing to poor concentration, emotional changes, impaired sleep quality and difficulties in performing daily tasks ( 82 , 83 ). Due to the typical symptoms, including sweating, shaking, chills, rapid heartbeat, poor mental state and hyperventilation, anxiety was defined as a specific psychiatric disorder ( 37 ).…”
Section: Effects and Mechanisms Of Exercise On Anxietymentioning
confidence: 99%
“…According to previous studies, nearly one-half of people diagnosed with depression will also experience comorbid anxiety ( 81 ). Anxiety is one of the most common mental health diseases contributing to poor concentration, emotional changes, impaired sleep quality and difficulties in performing daily tasks ( 82 , 83 ). Due to the typical symptoms, including sweating, shaking, chills, rapid heartbeat, poor mental state and hyperventilation, anxiety was defined as a specific psychiatric disorder ( 37 ).…”
Section: Effects and Mechanisms Of Exercise On Anxietymentioning
confidence: 99%
“…Secondly, it has been suggested that high levels of trait anxiety and anxiety disorders can influence how EFEs are perceived and interpreted (Dijk et al, 2018 ; Ewbank et al, 2009 ; Ferguson et al, 2021 ; Mennin et al, 2009 ; Yu et al, 2018 ). For example, more anxious individuals tended to perceive neutral faces as more threatening (Cooney et al, 2006 ; Peschard & Philippot, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Both RTs and accuracy scores were coded whenever possible. Additionally, we coded whether the task stimuli were emotional or neutral, as previous research has found that anxious individuals tend to perform worse on emotional tasks, compared to tasks that lacked emotional content (Eysenck & Byrne, 1992;Yu et al, 2018). In cases where a task had multiple conditions (e.g., low vs.…”
Section: Coding Of Variablesmentioning
confidence: 99%